Product focus. Brevet tx: anti-embolism stockings for prevention and treatment of DVT. - Collier M (British Journal of Nursing, 1999)
This article highlights the incidence and aetiology of thrombi, in particular deep vein thrombosis (DVT) before discussing the clinical features, diagnostic techniques and management of patients with suspected or confirmed DVT. The prophylactic use of anti-embolism stockings is then reviewed, including relevant clinical evidence, with particular reference to one of the leading brands of stocking currently available, that of Brevert tx (Seton Scholl Healthcare). The action, features, benefits and application of this type of anti-embolic stocking are detailed.